CLIMATIC MIGRATION AND TRANSFORMATION OF LANDSCAPES IN UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article deals with key climatic changes and related transformations of landscapes in Uzbekistan. It analyzes long-term trends in temperature and precipitation, drought dynamics and desertification processes, as well as the degradation of the Urals as a result of the drying up of the Aral Sea. Special attention is paid to efforts to restore landscapes through reforestation on the Aral Sea bed and urban and rural adaptation initiatives. The findings confirm the need for an integrated approach to natural resource management and landscape architecture in the face of accelerating climate change. In this regard, he article proposes an innovative formula for calculating the “intensity of climate change in a particular region”.